Evaluating Elasticity-Science Process Skills (E-SPS) in Construction Instrumen through Rasch Modelling - Diki Chen; Heru Kuswanto; Mundilarto Mundilarto; Ika Pratiwi; Muslimin Boma; Yovita Salsa Brilliant Hanindy (AL-ISHLAH: Jurnal Pendidikan, 2024)
The assessment of material elasticity science process skills in high school students requires validated and reliable instruments. This study aims to develop and validate a set of multiple-choice questions using the Rasch model to ensure their suitability for educational assessments. This quantitative research employed a model approach based on the Rasch model. The instrument consisted of multiple-choice questions designed to evaluate material elasticity science process skills. The validation process included two stages: content validation and construct validation. Content validation involved eight practicing teachers as validators, while construct validation was conducted with a sample of 32 high school students. Data analysis was performed using MNSQ infit, MNSQ outfit, delta, discrimination index, item differential power, and item difficulty level, with the assistance of Quest data analysis software. The results of the analysis from Quest revealed that only 10 questions met the Rasch model criteria. Among these, question number six was identified as the most difficult. The validation process demonstrated that the developed questions are appropriate for assessing the targeted skills based on the Rasch model. The findings indicate that the validated instrument is reliable and suitable for evaluating material elasticity science process skills in high school students. This study underscores the importance of rigorous validation processes in developing educational assessments. The developed multiple-choice questions, validated through the Rasch model, are feasible for use in assessing material elasticity science process skills. Future research should explore the application of this instrument in various educational contexts to further confirm its reliability and effectiveness across different student demographics.